2007
DOI: 10.1111/j.1365-2648.2006.04132.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation in health‐promoting behaviour: influences on community‐dwelling older Chinese people

Abstract: When developing health promotion programmes to motivate community-dwelling older Chinese clients to participate in health-promoting behaviour and to minimize barriers, community nurses should include some activities to increase both the perceived self-efficacy and perceived benefits of health-promoting behaviour. Future studies should include more critical factors based on theories, empirical evidence and knowledge of culture with samples that are random and from more diverse community settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
0
17
1
2
Order By: Relevance
“…Other studies also found that aged women have managed their age-related changes by using compensatory strategies (Keller, Leventhal, & Larson, 1989;Ouwehand et al, 2007). Congruent with our findings, research on the management of age-related changes have also shown that to maintain their health and independence elderly people engage in physical activities and change their mealtime and the type of their food (Day, 2008;Dunér & Nordströ m, 2005;Hansen-Kyle, 2005;Hinck, 2004;Jamjan, Maliwan, Pasunant, Sirapo-Ngam, & Porthiban, 2002;Kwong & Kwan, 2007;Van Maanen, 2006); change their daily time schedule activity and lifestyle (Hansen-Kyle, 2005;Hinck, 2004;Loeb, 2006;Peel, McClure, & Bartlett, 2005); seek assistance for their daily activities (Hinck, 2004); and make alterations to their surrounding environment . Natural aging outcomes are signs of decline and chronic disease (Chen, 2003;Cyr, 2007).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Other studies also found that aged women have managed their age-related changes by using compensatory strategies (Keller, Leventhal, & Larson, 1989;Ouwehand et al, 2007). Congruent with our findings, research on the management of age-related changes have also shown that to maintain their health and independence elderly people engage in physical activities and change their mealtime and the type of their food (Day, 2008;Dunér & Nordströ m, 2005;Hansen-Kyle, 2005;Hinck, 2004;Jamjan, Maliwan, Pasunant, Sirapo-Ngam, & Porthiban, 2002;Kwong & Kwan, 2007;Van Maanen, 2006); change their daily time schedule activity and lifestyle (Hansen-Kyle, 2005;Hinck, 2004;Loeb, 2006;Peel, McClure, & Bartlett, 2005); seek assistance for their daily activities (Hinck, 2004); and make alterations to their surrounding environment . Natural aging outcomes are signs of decline and chronic disease (Chen, 2003;Cyr, 2007).…”
Section: Discussioncontrasting
confidence: 53%
“…Several studies confirmed the importance of communication and social support for the health and well being in aged people (Bryant et al, 2001;Cannuscio, Block, & Kawachi, 2003;Dunér & Nordströ m, 2005;Kwong & Kwan, 2007;McCann Mortimer, Ward, & Winefield, 2008;Nagalingam, 2007;Nicholson, 2009). Access to social capital (resources available to individuals and groups through social connections and social relations with others) enables older women to maintain productive, independent, and fulfilling lives.…”
Section: Coping Strategies Of Iranian Elderly Women 583mentioning
confidence: 81%
“…Lack of opportunities was also found to be a barrier in the two German studies [29,33] and in international research [19,22,24]. It remains unclear whether this lack of sports programmes and facilities is real or perceived.…”
Section: Discussionmentioning
confidence: 99%
“…Those who stated that they were not sufficiently physically active were asked for reasons hindering them. They were asked to answer whether they "agree", "partly agree", or "disagree" with the following statements representing frequently reported barriers in older adults [13,14,16,17,19,22-25,28,29] (Table 1):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation